Clinically meaningful benefit and real‐world evidence in Alzheimer's disease research and care - Robert Perneczky; Lutz Froelich (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract In the realm of medical research, assessing novel therapies extends beyond statistical significance. The concept of meaningful benefits plays a pivotal role in determining the practical impact of interventions on patient outcomes. Clinical trials, which form the bedrock of evidence‐based medicine, guide treatment decisions and shape health‐care practices. While statistical significance remains a fundamental criterion, it falls short in fully evaluating the clinical relevance of therapeutic interventions. Clinically meaningful benefits focus on tangible improvements in patient health and well‐being, transcending mere statistical thresholds. Key considerations include survival rates, symptom relief, functional status, and other patient‐oriented outcomes. Determining meaningful benefits varies across diseases, patient populations, and available treatments. Balancing statistical rigor with clinical relevance is crucial. Overpowered trials may detect smaller differences than anticipated, necessitating careful interpretation. Researchers must view trial results through a patient‐centric lens. Beyond survival, evaluating quality of life and side effects is equally relevant. Quantifying meaningful benefits involves metrics like numbers needed to treat and progression‐free survival. Consistency across outcomes matters, as clinicians weigh gains in survival against improvements in quality of life. The pursuit of meaningful benefits elevates clinical trials from mere statistical exercises to patient‐centered endeavors. Researchers, clinicians, and regulators must prioritize outcomes that genuinely matter to patients, ensuring that medical progress translates into meaningful improvements for them and their families.